The archaeology of difference : negotiating cross-cultural engagements in Oceania - Torrence, Robin; Clarke, Anne, 1959- (One world archaeology., 2000)
The Archaeology of Difference presents a new and radically different perspective on the archaeology of cross-cultural contact and engagement.